PENGARUH BEBAN KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN Studi Baitul Maal Hidayatullah - Veri Muldani; Ahmad Faisal (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2022)
Abstract :Baitul Maal Hidayatullah (BMH) is an amil zakat institution which is engaged in collecting zakat, infaq, alms, Waqf and grants as well as humanitarian social funds and company’s Corporate Social Responsibility (CSR), distributes through educational programs, social da'wah, humanitarian and economic in national based. Based on the documentation data at BMH, it informs that employee performance does not comply with the targets set by the management. The purpose of this study was to examine the effect of workload, job satisfaction, and organizational commitment on employee performance.This study uses a quantitative approach with an explanatory or causal design. The population in this study were all employees at BMH. The type of data used is secondary data in the form of a questionnaire. Selection of the number of samples using the probability sampling method, the number of samples determined using the Slovin formula, and determined as many as 100 respondents. Data analysis using path analysis. The results found that workload affects organizational commitment, job satisfaction affects organizational commitment, workload affects employee performance, job satisfaction affects employee performance, organizational commitment affects employee performance.Keywords : Workload, Job Satisfaction, Organizational Commitment, Employee Performance.